2012
DOI: 10.4088/jcp.11m07413
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Transcranial Magnetic Stimulation in Clinical Practice Post-FDA Approval in the United States

Abstract: Adjunctive TMS was found to be safe and effective in both acute and maintenance treatment of patients with treatment-resistant depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 0 publications
8
45
1
Order By: Relevance
“…TMS uses brief magnetic field pulses to induce electrical currents in the cerebral cortex, which impacts a number of processes involved in brain function (Chervyakov et al, 2015). TMS for TRD in the general adult population has demonstrated safety, tolerability, and efficacy in multiple randomized controlled trials (e.g., George et al, 2010; Levkovitz et al, 2015; O'Reardon et al, 2007); similar outcomes have been reported in naturalistic effectiveness research (Carpenter et al, 2012) and retrospective case reviews (Connolly et al, 2012). However, TMS outcomes among older adults (≥60 years) with TRD remain unclear.…”
Section: Introductionmentioning
confidence: 66%
“…TMS uses brief magnetic field pulses to induce electrical currents in the cerebral cortex, which impacts a number of processes involved in brain function (Chervyakov et al, 2015). TMS for TRD in the general adult population has demonstrated safety, tolerability, and efficacy in multiple randomized controlled trials (e.g., George et al, 2010; Levkovitz et al, 2015; O'Reardon et al, 2007); similar outcomes have been reported in naturalistic effectiveness research (Carpenter et al, 2012) and retrospective case reviews (Connolly et al, 2012). However, TMS outcomes among older adults (≥60 years) with TRD remain unclear.…”
Section: Introductionmentioning
confidence: 66%
“…Connolly et al (2012) (19) reported data from the first 100 patients treated at their university-based TMS clinical service following FDA approval. Their cohort was also treatment resistant, with a mean of 3.4 failed adequate antidepressant trials in the current episode.…”
Section: ) Transcranial Magnetic Stimulation (Tms) For Acute Treatmementioning
confidence: 99%
“…Since initial FDA clearance, only a few studies have examined therapeutic response in actual clinical settings using the parameters under which the treatment was approved (>3000 pulses/session, minimum of 20 sessions, goal of 120% motor threshold). One study of 85 patients from a single academic center reported response and remission rates of 50.6% and 24.7%, respectively (Connolly et al, 2012), while a multi-site, naturalistic study of 307 patients (Carpenter et al, 2012), mostly in non-academic settings, found clinician-rated response and remission rates of 58% and 37%, respectively. However, with limited data, it remains an open question as to how rTMS is faring in regular clinical practice.…”
Section: Introductionmentioning
confidence: 99%